(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Cystinuria is an inherited disorder affecting luminal transport of cystine and dibasic amino acids. Because of the poor solubility of cystine in urine, stone formation in the kidney occurs frequently. Cystinuria is associated with mutations in the SLC3A1 and SLC7A9 genes. Despite the population-specific distribution of mutations in the SLC7A9 genes, there are few genetic data reported for cystinuric patients from the Middle East. Materials and Methods. Exon 4 of the SLC7A9 gene was sequenced in 21 patients with cystinuria, using the polymerase chain reaction and sequencing methods. Results. A new variation in exon 4 of the SLC7A9 gene was identified, which was insertion of 1 adenine nucleotide between 2 cytosine nucleotides in position c.213-214insA. Conclusions. It seems to be important since it causes frame shift and it may be an important cause to make disease.